Ageratina adenophora (Spreng.) King & H. Rob. Standardized leaf extract as an antidiabetic agent for type 2 diabetes: An in vitro and in vivo evaluation - Chanu, Khaidem Devika; Sharma, Nanaocha; Kshetrimayum, Vimi; Chaudhary, Sushil Kumar; Ghosh, Suparna; Haldar, Pallab Kanti; Mukherjee, Pulok K. (Frontiers in Pharmacology, 2023)
Type 2 diabetes has become one of the major health concerns of the 21st century, marked by hyperglycemia or glycosuria, and is associated with the development of several secondary health complications. Due to the fact that chemically synthesized drugs lead to several inevitable side effects, new antidiabetic medications from plants have gained substantial attention. Thus, the current study aims to evaluate the antidiabetic capacity of the Ageratina adenophora hydroalcoholic (AAHY) extract in streptozotocin–nicotinamide (STZ–NA)-induced diabetic Wistar albino rats. The rats were segregated randomly into five groups with six rats each. Group I was normal control, and the other four groups were STZ–NA-induced. Group II was designated diabetic control, and group III, IV, and V received metformin (150 mg/kg b.w.) and AAHY extract (200 and 400 mg/kg b.w.) for 28 days. Fasting blood glucose, serum biochemicals, liver and kidney antioxidant parameters, and pancreatic histopathology were observed after the experimental design. The study concludes that the AAHY extract has a significant blood glucose lowering capacity on normoglycemic (87.01 ± 0.54 to 57.21 ± 0.31), diabetic (324 ± 2.94 to 93 ± 2.04), and oral glucose-loaded (117.75 ± 3.35 to 92.75 ± 2.09) Wistar albino rats. The in vitro studies show that the AAHY extract has α-glucosidase and α-amylase inhibitory activities which can restore the altered blood glucose level, glycated hemoglobin, body weight, and serum enzymes such as serum glutamic pyruvic transaminase, serum glutamic oxaloacetic transaminase, serum alkaline phosphatase, total protein, urea, and creatinine levels close to the normal range in the treated STZ–NA-induced diabetic rats. The evaluation of these serum biochemicals is crucial for monitoring the diabetic condition. The AAHY extract has significantly enhanced tissue antioxidant parameters, such as superoxide dismutase, glutathione, and lipid peroxidation, close to normal levels. The presence of high-quantity chlorogenic (6.47% w/w) and caffeic (3.28% w/w) acids as some of the major phytoconstituents may contribute to the improvement of insulin resistance and oxidative stress. The study provides scientific support for the utilization of A. adenophora to treat type 2 diabetes in the STZ–NA-induced diabetic rat model. Although the preventive role of the AAHY extract in treating Wistar albino rat models against type 2 diabetes mellitus is undeniable, further elaborative research is required for efficacy and safety assessment in human beings.